Mortality trend analysis of schistosomiasis in the Philippines from 1960-2019 - Jamerah Baniaga Sidic; Angel Mae Frias Luga; Kathleen Laum Cabanlit; Ralf Benjo Goder Morilla; Chin-Chin Jimena Demayo; Cesar Guinanao Demayo (International Journal of Public Health Science (IJPHS), 2023)
Despite the different reviews and publications about schistosomiasis disease, it remains an economic and public health problem in the Philippines. Thereby, this study examined the trends of schistosomiasis mortality in the Philippines over 60 years concerning sex, age, and region-specific, using the data from the Philippine Health Statistics. Results show that national mortality rates have decreased from 1960-2019. The trend in schistosomiasis sex-specific mortality rates showed that men had a greater schistosomiasis- related death rate than women. For the age-specific mortality rate, children under the age of 1 have the lowest death rate compared with people over 70 having the highest death rate. For the region-specific mortality, Region VIII (Eastern Visayas) has the highest mortality rate with a value of 4, and Region XI (Davao) has the highest morbidity rate with a value of 53. To fully eradicate schistosomiasis in the succeeding years, an extensive transmission control measure and awareness education program must be implemented locally and nationally.